Total Harmonics Distortion of 5 Level and 3 Level Inverter using Proportional Resonant Controller - Nadzar, Imran Hakimi; Salimin, Suriana (Evolution in Electrical and Electronic Engineering, 2021)
Total harmonics distortion (THD) is the main problem of an inverters. Most of the harmonic currents and voltages flow in the load are frequencies that are higher than the fundamental supply frequencies, where it then generates more heat and increases the possibility of equipment malfunction. Harmonics are the additional current and voltages doesn’t contribute any mechanical force to the motors, instead, it is simply dissipated as heat in the load, thus may cause premature equipment failure and can cause equipment malfunction. In order to mitigate these harmonic problems, a proportional resonant (PR) is used in this work. The cascaded 5 level inverter topology is incorporated to suppress the harmonics produced by the inverter at its output. Results of the THD current are then compared between the 3 level and 5 level inverters.